E-Commerce: How Can Businesses Benefit From E-Commerce? - Amca, Hasan; Jönsson, Anders (International Conference on Contemporary Issues in Information Technology in OIC Member States, 2005)
E-business in general and e-commerce in particular is changing the way people do business and sell their product and services to the entire world without the need of physically existing around the globe. As enterprises exploit business opportunities via the Internet, they have discovered that not only they need a reliable and scalable IT infrastructure to support their online business, but also they must have the capability to deploy new online applications rapidly and integrate e-commerce to their already existing business model. The paper concentrates on the description of e-commerce, how businesses transform to e-commerce and the technical details about the necessary IT infrastructure, business model for the transformation, payment schemes and success factors.
About Authors: Hasan Amca, Dean of Facult of Engineering, Eastern Mediterranean University, Famagusta,TRNC. and Anders Jönsson, E-Commerce Specialist, UNDP Partnership for the Future, Nicosia,Cyprus.
Keywords: Global Economics - E-Commerce - E- Business; E-Commerce - Technology; E- Commerce - Legal Framework; Security, Payment Issues; E-Commerce - Business; Commercial Networks; Business Opportunities; Attractive Market